A Biomimetic Adapter for Passive Self-alignment of Prosthetic Feet. (25th January 2021) - Rajula, Vamsidhar Reddy; Springgate, Logan; Haque, Aman; Kamrunnahar, Mst; Piazza, Stephen J; Kaluf, Brian
ABSTRACT: Introduction: Dynamic alignment of lower limb prostheses is subjective and time-consuming. Compensatory gait strategies caused by prosthesis misalignment can negatively affect lower limb amputees who cannot access a certified prosthetist for alignment adjustments. The objective of this study is to evaluate a novel six-degrees-of-freedom passive transtibial prosthetic adapter that self-aligns during various phases of gait. This self-aligning adapter may benefit service members and veterans stationed or living far from a clinical facility. Methods: Four transtibial amputee subjects, aged 47 to 62 (mean: 55.75) years with mean weight of 163.6 lbs and mean K-level of 3.25, walked at self-selected speeds on a 10-m level walkway. Subjects walked with the self-aligning and a size- or weight-matched control adapter, assembled to a commercially available energy-storing-and-returning foot and their own socket, with 22-mm alignment perturbations in the anterior, posterior, medial, or lateral directions. Subjects were blinded to both adapter type and misalignment. Socket moments, spatiotemporal gait parameters, and subjective socket comfort were recorded. Results: Preliminary results showed improvements in mean peak socket moments and step length differential with the self-aligning adapter across all alignments. Walking speed and prosthesis-side base of support showed little change in all configurations. Prosthesis-side stance duration and Functional Ambulation Profile Score increased with the self-aligning adapter in some alignments. Patient-reported socket comfort increased slightly with the self-aligning adapter across all misalignments. Conclusion: Subjects maintained similar walking speeds and experienced greater gait symmetry and reduced sagittal plane peak moments with the self-aligning adapter when exposed to misalignments. These trends suggest a benefit to transtibial amputees from a reduction in secondary gait effects from prosthesis misalignments. Additionally, a wider range of acceptable prosthesis alignments may be possible with the self-aligning adapter. Subsequent trials are underway to evaluate the self-aligning adapter in real-world environments like walking on uneven terrains, stairs, ramps, and abrupt turns.